Cross-linked aromatic polyester resin composition and method for manufacturing the same
Patent Information
- Application Number
- KR1020237016312
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-16
- Filing Date
- 2021-10-14
- Publication Date
- 2026-10-21
- Estimated Expiration
- 2041-10-14
Smart Images

Figure 112023053132520-PCT00001 
Figure 112023053132520-PCT00002 
Figure 112023053132520-PCT00003
Abstract
Description
Technology Field
[0001] The present invention relates to a cross-linked aromatic polyester resin composition exhibiting self-adhesion, remolding, and self-repair properties under high temperature conditions, and a method for preparing the same. More specifically, the invention relates to an aromatic polyester composition having a stable cross-linked polymer network at room temperature and, at high temperatures, an intermolecular bond exchange reaction that activates, thereby softening the sample. Background Technology
[0002] Aromatic polyesters having carboxyl groups in their side chains and cross-linked polyesters cured from epoxy compounds have been conventionally used in the fields of adhesives and paints; however, due to the irreversibility of covalent crosslinking sites, they lack adhesiveness, remoldability, and restorability. On the other hand, films incorporating bond-exchange dynamic crosslinking can bond films together without the use of adhesives, thereby suppressing the leaching of foreign substances or residual solvents caused by adhesives, and thus can be films with excellent safety. Furthermore, aromatic polyesters are particularly useful industrially because they have excellent heat resistance and chemical resistance.
[0003] A cross-linked polyester resin has been reported by mixing an aliphatic polyester having carboxyl groups in its side chains, an aliphatic diepoxy having epoxy groups at both ends, and zinc acetate, and then heating to cross-link (Patent Document 1).
[0004] A resin composition obtained by mixing a thermoplastic resin containing hydroxyl groups, a thermoplastic resin containing ester bonds, and an ester exchange catalyst, and then heating to crosslinking has been reported (Patent Document 2). Prior art literature
[0005] Patent Document 1: WO 2020 / 045439 Patent Document 2: Japanese Patent Publication No. 2020-23591 The problem to be solved
[0006] However, the cross-linked polyester resin of Patent Document 1 is described as having an aliphatic polyester having a carboxyl group in its molecule as the base polymer, but an aromatic polyester is not described. The reason for this is that Patent Document 1 describes a method of synthesizing a polyester precursor containing a thiol group in its side chain by melt polycondensation of a diol component and thiomalic acid, which is a dicarboxylic acid containing a thiol group in its side chain, and obtaining a polyester resin containing a carboxyl group in its side chain by Michael addition reaction of the precursor with acrylic acid. However, in the case of the direct polymerization method of dicarboxylic acids and diols, it is common to carry out an esterification reaction between an aromatic dicarboxylic acid with a melting point of 300°C or higher and a diol at a high temperature (e.g., 200–240°C) above the boiling point of the diol, and there are technical reasons such as the high energy consumption during polycondensation, and the fact that terephthalic acid and isophthalic acid, which are commonly used as raw materials for aromatic polyesters, both have melting points of 300°C or higher and are difficult to handle due to their sublimable crystals. Furthermore, Patent Document 2 produces resin powders of a thermoplastic resin containing hydroxyl groups and a thermoplastic resin containing ester bonds, mixes them with an ester exchange catalyst, and then produces a flat plate using an injection molding machine, but this is substantially achieved only with acrylic resin, and there is a problem that acrylic resin has low heat resistance.
[0007] The present invention aims to provide a cross-linked aromatic polyester resin composition that, by using an aromatic polyester as a base polymer and enabling "dynamic" covalent crosslinking capable of bond exchange at high temperatures—which has been difficult to achieve until now—exhibits high strength at room temperature, enables reprocessing, adhesion between films, and self-repairability above the bond exchange activation temperature, and also possesses excellent heat resistance by containing an aromatic component. means of solving the problem
[0008] As a result of careful consideration, the inventors have discovered that the above problem can be solved by means described below, and thus have arrived at the present invention. That is, the present invention comprises the following configuration.
[0009] A cross-linked aromatic polyester resin composition containing a cross-linked aromatic polyester resin (C) and an ester exchange catalyst (D), satisfying the following (1) to (2).
[0010] (1) The cross-linked aromatic polyester resin (C) is a reaction product of an aromatic polyester resin (A) containing carboxyl groups in its side chains and an epoxy compound (B).
[0011] (2) When the above cross-linked aromatic polyester resin composition was measured by infrared spectroscopy, the wavenumber derived from the ester bond was 1730 cm⁻¹ -1 Absorbance of the peak in the vicinity (A 1730 Regarding ), wavenumber derived from the hydroxyl group 3200–3600 cm -1 Absorbance of the peak in the vicinity (A 3200-3600 The ratio of ) (A 3200-3600 / A 1730 ) is 0.005 or greater and 0.038 or less.
[0012] It is preferable that the acid value of the aromatic polyester resin (A) containing a carboxyl group in the above side chain is 5 mgKOH / g or more and 120 mgKOH / g or less, and the number average molecular weight is 8000 or more.
[0013] It is preferable that the molar ratio (carboxyl group:epoxy group) of the epoxy group of the epoxy compound (B) to the carboxyl group of the aromatic polyester resin (A) having a carboxyl group in the side chain is 100:50 to 100:150.
[0014] It is preferable that the number average molecular weight of the above epoxy compound (B) is 100 or more and 500 or less.
[0015] It is preferable that the molar ratio (carboxyl group:ester exchange catalyst) of the ester exchange catalyst (D) to the carboxyl group of the aromatic polyester resin (A) having a carboxyl group in the above side chain is 100:10 to 100:40.
[0016] A method for preparing a cross-linked aromatic polyester resin composition, comprising the process of mixing an aromatic polyester resin (A) containing carboxyl groups in a side chain having an acid value of 5 mgKOH / g or more and 120 mgKOH / g or less, an epoxy compound (B), and an ester exchange catalyst (D), and heating to crosslink.
[0017] A self-adhesive agent, self-repairing material, or molding material containing the above-mentioned cross-linked aromatic polyester resin composition. Effects of the invention
[0018] The cross-linked aromatic polyester resin composition of the present invention, through "dynamic" covalent crosslinking capable of bond exchange at high temperatures, exhibits high strength at room temperature and enables reprocessing and adhesion between films above the bond exchange activation temperature. Furthermore, due to the remolding processability of the cross-linked aromatic polyester resin composition, molding or thinning is possible after the crosslinking reaction, and damage can be repaired through self-healing properties, allowing for semi-permanent use. Specific details for implementing the invention
[0019] The cross-linked aromatic polyester resin composition is a resin composition containing an aromatic polyester resin (A) having carboxyl groups in its side chains (hereinafter also simply referred to as "aromatic polyester resin having carboxyl groups in its side chains (A)" or "polyester resin (A)"), a cross-linked aromatic polyester resin (C) which is a reactant of an epoxy compound (B), and an ester exchange catalyst (D).
[0020] <Aromatic polyester resin containing carboxyl groups in the side chain (A)>
[0021] An aromatic polyester resin (A) containing a carboxyl group in a side chain is a resin having a carboxyl group in a side chain of the aromatic polyester resin. Here, the side chain may be a structure having a carboxyl group on a substituent (e.g., an aliphatic hydrocarbon group, an aromatic hydrocarbon group, alicyclic hydrocarbon group, etc.) branched from the main chain of the aromatic polyester resin, or it may be a structure having a carboxyl group directly in the aromatic polyester resin. Preferably, it is a structure having a carboxyl group directly in the aromatic polyester resin.
[0022] It is preferable that the acid value of the polyester resin (A) be 5 mgKOH / g or higher. More preferably, it is 10 mgKOH / g or higher, and even more preferably 15 mgKOH / g or higher, for the reason that sufficient crosslinking improves heat resistance. In addition, it is preferable that the acid value be 120 mgKOH / g or lower. More preferably, it is 110 mgKOH / g or lower, and even more preferably 100 mgKOH / g or lower, for the reason that the crosslinking density increases and the coating film obtained from the crosslinked aromatic polyester resin composition can be prevented from becoming excessively hard.
[0023] The polyester resin (A) preferably contains ester bonds and carboxyl groups at multiple points within the molecule. In particular, it is more preferable to include 2 or more carboxyl groups in the molecular chain, even more preferable to include 3 or more, and even more preferable to include 4 or more. The number of carboxyl groups per molecular chain (N COOH The upper limit of ) is not specifically limited, but it is good if it is 50 points or less, and it is acceptable if it is 30 points or less.
[0024] The number average molecular weight (Mn) of an aromatic polyester resin (A) containing carboxyl groups in its side chains is preferably 8,000 or more, more preferably 10,000 or more, and even more preferably 12,000 or more. Additionally, the number average molecular weight is preferably 30,000 or less, more preferably 25,000 or less, and even more preferably 20,000 or less. By keeping it within the above range, it becomes easier to control the acid value of the polyester resin (A).
[0025] The glass transition temperature of the polyester resin (A) is preferably -10°C or higher, more preferably 0°C or higher, and even more preferably 5°C or higher. In addition, the glass transition temperature is preferably 100°C or lower, more preferably 80°C or lower, and even more preferably 60°C or lower.
[0026] An aromatic polyester resin (A) containing a carboxyl group in a side chain needs to have a side chain (hereinafter also referred to as a branched structure) and an aromatic group within the molecule. In order for the polyester resin (A) to have a branched structure and an aromatic group, it is preferable that the copolymer component that serves as the raw material has a branched structure and an aromatic group. The polyester resin (A) may be obtained by (i) reacting (copolymerizing) a polymeric polyol with a chain extender, etc., or (ii) by adding a monomer having a carboxyl group to a polyester having a reaction site obtained by the reaction of a polycarboxylic acid component and a polyalcohol component.
[0027] In case (i), at least one of the polymer polyol and / or chain extender may have a branched structure and the other may have an aromatic group, or one may have both a branched structure and an aromatic group. One or more types of polymer polyols may be used in combination. When two or more types of polymer polyols are used in combination, one polymer polyol may have a branched structure and the other may have an aromatic group, or one may have both a branched structure and an aromatic group. Additionally, in case (ii), at least one of the polyester and / or addition monomer having a carboxyl group may have an aromatic group, or both may have aromatic groups.
[0028] As a polycarboxylic acid component used in an aromatic polyester resin (A) containing a carboxyl group in a side chain, it is preferable that it be an aromatic dicarboxylic acid component. As an aromatic dicarboxylic acid component, it is not particularly limited and may include terephthalic acid, isophthalic acid, orthophthalic acid, naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, and diphenic acid. In addition, aromatic dicarboxylic acids having a sulfonic acid group such as sulfoterephthalic acid, 5-sulfoisophthalic acid, 4-sulfophthalic acid, 4-sulfonaphthalene-2,7-dicarboxylic acid, and 5(4-sulfophenoxy)isophthalic acid, and aromatic dicarboxylic acids having a sulfonate group such as their metal salts and ammonium salts may be used. These may be used alone or in combination of two or more types. Among these, terephthalic acid, isophthalic acid, and mixtures thereof are particularly desirable in that they increase the cohesiveness of the coating film.
[0029] Other polycarboxylic acid components include alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid and their acid anhydrides, aliphatic dicarboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanetic acid, and dimer acid, and dicarboxylic acids containing unsaturated bonds such as maleic acid, fumaric acid and their acid anhydrides. In addition, oxycarboxylic acid compounds having hydroxyl and carboxyl groups in their molecular structures, such as 5-hydroxyisophthalic acid, p-hydroxycyanoic acid, p-hydroxyphenylalcohol, p-hydroxyphenylpropionic acid, p-hydroxyphenylacetic acid, 6-hydroxy-2-naphthoic acid, and 4,4-bis(p-hydroxyphenyl)valeric acid, and thiomalic acid having thiol groups in their molecular structures can also be used.
[0030] As a polyalcohol component used in an aromatic polyester resin (A) containing carboxyl groups in its side chains, it is preferable that it be a glycol component. As a glycol component, it is preferable that it be an aliphatic glycol, alicyclic glycol, an aromatic glycol, or an ether-linked glycol.
[0031] Examples of aliphatic glycols include ethylene glycol, 1,2-propylene glycol, 1,3-propanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, 2-methyl-1,3-butanediol, 1,5-pentanediol, 2,2-dimethyl-1,3-propanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,9-nonanediol, 2-ethyl-2-butylpropanediol (DMH), hydroxypivalate neopentyl glycol ester, dimethylolheptane, 2,2,4-trimethyl-1,3-pentanediol, etc.
[0032] Examples of cycloaliphatic glycols include 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, tricyclodecanediol, tricyclodecanedimethylol, spiroglycol, hydrogenated bisphenol A, ethylene oxide adducts and propylene oxide adducts of hydrogenated bisphenol A, etc.
[0033] Examples of aromatic glycols include paraxylene glycol, metaxylene glycol, orthoxylene glycol, 1,4-phenylene glycol, ethylene oxide adduct of 1,4-phenylene glycol, bisphenol A, ethylene oxide adduct of bisphenol A and propylene oxide adduct, glycols obtained by adding 1 to several moles of ethylene oxide or propylene oxide to each of two phenolic hydroxyl groups of bisphenols. Additionally, specific examples of glycol modified products of aromatic dicarboxylic acids are not particularly limited, but include bis-2-hydroxyethyl terephthalate (BHET), which is an ethylene glycol modified product of terephthalic acid, a propylene glycol modified product of terephthalic acid, an ethylene glycol modified product of isophthalic acid, a propylene glycol modified product of isophthalic acid, an ethylene glycol modified product of orthophthalic acid, and a propylene glycol modified product of orthophthalic acid. In addition, other examples of glycol modified products of aromatic dicarboxylic acids include naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, diphenic acid, 5-hydroxyisophthalic acid, sulfoterephthalic acid, 5-sulfoisophthalic acid, 4-sulfophthalic acid, 4-sulfonaphthalene-2,7-dicarboxylic acid, 5-(4-sulfophenoxy)isophthalic acid, sulfoterephthalic acid, and / or glycol modified products of aromatic dicarboxylic acids having sulfonic acid groups or sulfonate groups, such as metal salts or ammonium salts thereof.
[0034] Examples of glycols containing ether bonds include diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, neopentyl glycol ethylene oxide adduct, neopentyl glycol propylene oxide adduct, etc.
[0035] These can be used alone or in combination of two or more types.
[0036] As a polymer polyol used in an aromatic polyester resin (A) containing carboxyl groups in its side chains, it is preferable that the polymer polyol be a copolymer of the polycarboxylic acid component and the polyol component (polymer polyester polyol). In addition, to impart an acid value to the polymer polyol, it is also preferable to add acid using a polycarboxylic acid compound with three or more functions.
[0037] Examples of polycarboxylic acid components with three or more functions include compounds such as trimellitic acid, trimesic acid, ethylene glycol bis(anhydrotrimellitate), glycerol tris(anhydrotrimellitate), trimellitic anhydride, pyrromellitic anhydride (PMDA), oxydiphthalic anhydride (ODPA), 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride (BTDA), 3,3',4,4'-diphenyltetracarboxylic acid dianhydride (BPDA), 3,3',4,4'-diphenylsulfone tetracarboxylic acid dianhydride (DSDA), 4,4'-(hexafluoroisopropylidene)diphthalic acid dianhydride (6FDA), and 2,2'-bis[(dicarboxyphenoxy)phenyl]propane dianhydride (BSAA). Meanwhile, examples of polyols with three or more functions include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol.
[0038] The number average molecular weight (Mn) of the polymer polyol is preferably 1000 or more, more preferably 2000 or more, and even more preferably 3000 or more. In addition, the number average molecular weight is preferably 30000 or less, more preferably 25000 or less, and even more preferably 20000 or less.
[0039] The acid value of the polymer polyol is preferably 0.1 mgKOH / g or higher, more preferably 0.2 mgKOH / g or higher, and even more preferably 0.3 mgKOH / g or higher. In addition, the acid value is preferably 20 mgKOH / g or lower, more preferably 15 mgKOH / g or lower, and even more preferably 10 mgKOH / g or lower.
[0040] The glass transition temperature of the above polymer polyol is preferably -10°C or higher, more preferably 0°C or higher, and even more preferably 5°C or higher. In addition, the glass transition temperature is preferably 100°C or lower, more preferably 80°C or lower, and even more preferably 60°C or lower.
[0041] As chain extenders, tetracarboxylic acid dianhydrides are not particularly limited, but can be used.
[0042] Examples of tetracarboxylic acid dianhydrides include aromatic tetracarboxylic acid dianhydrides, aliphatic tetracarboxylic acid dianhydrides, or alicyclic tetracarboxylic acid dianhydrides, and aromatic tetracarboxylic acid dianhydrides are preferred. Specifically, examples include pyromolytic anhydride (PMDA), oxydiphthalic anhydride (ODPA), 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride (BTDA), 3,3',4,4'-diphenyltetracarboxylic acid dianhydride (BPDA), 3,3',4,4'-diphenylsulfone tetracarboxylic acid dianhydride (DSDA), 4,4'-(hexafluoroisopropylidene)diphthalic acid dianhydride (6FDA), and 2,2'-bis[(dicarboxyphenoxy)phenyl]propane dianhydride (BSAA), and these may be used alone or in combination of two or more. Among these, pyromolytic anhydride is preferred.
[0043] As for the copolymerization ratio of the polymer polyol and the chain extender, it is preferable that the chain extender be 0.5 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 2 parts by mass or more, with respect to 100 parts by mass of the polymer polyol. In addition, it is preferable that the chain extender be 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less, with respect to 100 parts by mass of the polymer polyol.
[0044] In the aromatic polyester resin (A) containing carboxyl groups in the side chain, a polyester containing carboxyl groups at multiple points is preferably used. There are two methods for introducing an acid value into the polyester resin (A).
[0045] As a first method, a carboxylic acid can be introduced into a polyester polyol by acid addition after polymerization. Since using monocarboxylic acids, dicarboxylic acids, or polycarboxylic acid compounds with three or more functions for acid addition may result in a decrease in molecular weight due to ester exchange, it is preferable to use a compound having at least one carboxylic acid anhydride group.
[0046] Examples of carboxylic acid anhydrides include succinic anhydride, maleic anhydride, phthalic anhydride, 2,5-norbornene dicarboxylic acid anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, pyrromellitic anhydride (PMDA), oxydiphthalic acid dianhydride (ODPA), 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride (BTDA), 3,3',4,4'-diphenyltetracarboxylic acid dianhydride (BPDA), 3,3',4,4'-diphenylsulfone tetracarboxylic acid dianhydride (DSDA), 4,4'-(hexafluoroisopropylidene)diphthalic acid dianhydride (6FDA), 2,2'-bis[(dicarboxyphenoxy)phenyl]propane dianhydride (BSAA), etc.
[0047] As a second method, a polyester precursor containing double bond sites at multiple points is obtained by melt polycondensation using maleic acid, with a glycol modified product of an aromatic dicarboxylic acid as the diol component. When this precursor is reacted with, for example, thioglycolic acid, a polyester resin (A) containing carboxyl groups at multiple points in the side chain can be obtained through a Michael addition reaction between the double bond sites derived from maleic acid and the thiol group.
[0048] <Epoxy Compound (B)>
[0049] As for the epoxy compound (B), it is not particularly limited, but it is preferable to be a compound having two or more epoxy groups in a molecule. As for the compound having two or more epoxy groups in a molecule (epoxy crosslinking agent), it is not particularly limited as long as it reacts with the carboxyl groups of the polyester resin (A) to form crosslinks, but it is preferable to be a polyfunctional epoxy compound having multiple epoxy groups in one molecule. By using a polyfunctional epoxy compound, the cured film obtained from the crosslinked aromatic polyester resin composition can easily form three-dimensional crosslinks, making it possible to improve heat resistance.
[0050] Examples of multifunctional epoxy compounds include cresol novolak-type epoxy compounds, epoxy compounds having a dicyclopentadiene backbone, and phenol novolak-type epoxy compounds. These may be used alone or in combination of two or more types.
[0051] In addition, in addition to the above-mentioned multifunctional epoxy compound, an epoxy compound containing nitrogen atoms may also be used. It is preferable to use an epoxy compound containing nitrogen atoms in combination, as this allows the coating film of the resin composition to be brought to a semi-cured state by heating at a relatively low temperature, and also allows for the expectation of an effect that suppresses foaming.
[0052] Examples of epoxy compounds containing nitrogen atoms include, for instance, tetraglycidyl diaminodiphenylmethane, triglycidyl para-aminophenol, tetraglycidyl bisaminomethylcyclohexanone, and glycidylamine-based compounds such as N,N,N',N'-tetraglycidyl-m-xylenediamine.
[0053] Examples of commercially available epoxy compounds containing nitrogen atoms include "TETRAD-X" (product name) manufactured by Mitsubishi Gas Co., Ltd. and "jER630" (product name) manufactured by Mitsubishi Chemical Co., Ltd.
[0054] Other epoxy compounds may also be used as the epoxy compound (B) used in the present invention. Examples include glycidyl ether types such as bisphenol A diglycidyl ether, bisphenol S diglycidyl ether, and brominated bisphenol A diglycidyl ether; glycidyl ester types such as hexahydrophthalic acid glycidyl ester and dimer acid glycidyl ester; triglycidyl isocyanurate, 3,4-epoxycyclohexylmethylcarboxylate, epoxidized polybutadiene, and epoxidized soybean oil; and alicyclic or aliphatic epoxides such as epoxidized polybutadiene and epoxidized soybean oil. One type may be used alone, or two or more types may be used in combination.
[0055] The number average molecular weight (Mn) of the epoxy compound (B) is preferably 100 or more and 500 or less in terms of crosslinking density, and more preferably 200 or more and 400 or less.
[0056] <Cross-linked aromatic polyester resin (C)>
[0057] The cross-linked aromatic polyester resin (C) is a reaction product of the polyester resin (A) and the epoxy compound (B). The reaction may be carried out in the absence of a solvent or in the presence of an organic solvent.
[0058] The organic solvent is not particularly limited as long as it does not react with the polyester resin (A), the epoxy compound (B), and the cross-linked aromatic polyester resin (C). Examples include aromatic organic solvents such as toluene and xylene, aliphatic organic solvents such as heptane and octane, ether-based solvents such as tetrahydrofuran and diethyl ether, and amide-based solvents such as dimethylformamide and N-methylpyrrolidone. These may be used individually or in combination of two or more.
[0059] The above reaction temperature is preferably 80°C or higher, more preferably 100°C or higher, and even more preferably 120°C or higher. In addition, it is preferably 200°C or lower, more preferably 180°C or lower, and even more preferably 160°C or lower.
[0060] The above reaction time, depending on the reaction temperature, is preferably 30 minutes or more, more preferably 1 hour or more, and even more preferably 2 hours or more. In addition, it is preferably within 10 hours, more preferably within 8 hours, and even more preferably within 5 hours.
[0061] The ratio of the mixture of polyester resin (A) and epoxy compound (B) can be determined based on the molar ratio of functional groups between the carboxyl groups of the side chains of polyester resin (A) and the epoxy groups of epoxy compound (B). In terms of crosslinking reaction efficiency, the ratio of the epoxy groups of the epoxy compound (B) to the carboxyl groups of the polyester resin (A) (carboxyl groups:epoxy groups) is preferably 100:50 to 100:150 (molar parts), and more preferably 100:80 to 100:120 (molar parts).
[0062] <Ester exchange catalyst (D)>
[0063] The ester exchange catalyst (D) is an ester exchange catalyst for the ester groups in the polyester resin (A). Through the ester exchange catalyst (D), the cross-linked aromatic polyester resin composition of the present invention undergoes "dynamic" covalent cross-linking, which allows for bond exchange at high temperatures. Consequently, it exhibits high strength at room temperature, and above the ester bond exchange activation temperature, it enables reprocessing and adhesion between films. Furthermore, due to the re-forming processability of the cross-linked aromatic polyester resin composition, molding or thin film formation is possible after the cross-linking reaction, and damage can be repaired through self-healing properties, allowing for semi-permanent use. The ester bond exchange activation temperature of the cross-linked aromatic polyester resin composition can be determined as a softening temperature based on the inflection point of the change in linear expansion coefficient.
[0064] Examples of ester exchange catalysts (D) include zinc acetate, triphenylphosphine, 1,5,7-triazabicyclo[4.4.0]deca-5-ene, 1,8-diazabicyclo[5.4.0]undecene-7, etc., and among these, zinc acetate is preferred.
[0065] The amount of the ester exchange catalyst (D) mixed is preferably 10 to 40 moles per 100 moles of the carboxyl groups of the polyester resin (A), and more preferably 15 to 30 moles, in terms of the mechanical strength of the polyester resin (A) or the uniformity of the sample.
[0066] <Cross-linked aromatic polyester resin composition>
[0067] The cross-linked aromatic polyester resin composition is a composition containing the cross-linked aromatic polyester resin (C) and the ester exchange catalyst (D).
[0068] The cross-linked aromatic polyester resin composition has a wavenumber of 1730 cm⁻¹ derived from the ester bond when measured by infrared spectroscopy. -1 Absorbance of the peak in the vicinity (A 1730Regarding ), wavenumber derived from the hydroxyl group 3200–3600 cm -1 Absorbance of the peak in the vicinity (A 3200-3600 The ratio of ) (A 3200-3600 / A 1730 ) is 0.005 or greater and 0.038 or less. As a reason for improved self-restoring ability, remodeling ability, and damage restoring ability, the ratio (A 3200-3600 / A 1730 ) is preferably 0.007 or higher, and more preferably 0.01 or higher. In addition, the ratio (A 3200-3600 / A 1730 ) is preferably 0.035 or less, and more preferably 0.03 or less. The measurement method of infrared spectroscopy follows the description in the example.
[0069] An example of a method for preparing a cross-linked aromatic polyester resin composition is provided. The cross-linked aromatic polyester resin composition can be obtained by mixing a polyester resin (A), an epoxy compound (B), and an ester exchange catalyst (D), heating the mixture, and performing a cross-linking reaction through an epoxy ring-opening reaction. The order of mixing the polyester resin (A), the epoxy compound (B), and the ester exchange catalyst (D) is not particularly limited, but it is preferable to mix the polyester resin (A) and the epoxy compound (B), and then add the ester exchange catalyst (D) to perform the cross-linking reaction.
[0070] The softening temperature of the cross-linked aromatic polyester resin composition is preferably 100°C or higher, more preferably 110°C or higher, and even more preferably 120°C or higher. The upper limit of the softening temperature is not particularly limited, but industrially it is acceptable to have it at 300°C or lower, and 250°C or lower.
[0071] The temperature at which the weight of the cross-linked aromatic polyester resin composition decreases by 5% when heated (5% weight loss temperature) is preferably 230°C or higher, 250°C or higher, more preferably 280°C or higher, and even more preferably 300°C or higher. The upper limit of the 5% weight loss temperature is not particularly limited, but industrially it is preferable to be 500°C or lower, and 450°C or lower is acceptable. The 5% weight loss temperature can be used as an indicator of heat resistance.
[0072] Regarding the shape of the molded article made of the cross-linked aromatic polyester resin composition, various shapes are possible, but from the perspective of maintaining a sufficient adhesive area, a film shape is preferred. That is, the cross-linked aromatic polyester resin composition of the present invention can be used as a film-shaped adhesive and can be used as an adhesive between resin films, between metal foils, or between a resin film and a metal foil. Examples of resin films include polyimide films, polyester films, PET films, etc. Examples of metal foils include copper foil, silver foil, gold foil, etc. The adhesiveness of the cross-linked aromatic polyester resin composition can be evaluated based on the 90° peel strength shown in the examples.
[0073] Since the cross-linked aromatic polyester resin composition enables bond exchange by heating above the ester bond exchange activation temperature, when the cross-linked aromatic polyester resin composition is used as an adhesive material, the adhesive becomes easy to peel off by heating above the ester bond exchange activation temperature. Therefore, the cross-linked aromatic polyester resin composition can be used as a material for a peelable type of repair adhesive. The peelability of the cross-linked aromatic polyester resin composition when heated to a high temperature can be evaluated based on the 90° peel strength at heating shown in the examples.
[0074] A cross-linked aromatic polyester resin composition can be used as a laminating material. Since the cross-linked aromatic polyester resin composition has heat resistance, for example, by bonding a film using the cross-linked aromatic polyester resin composition to the surface of a resin molded body or a metal molded body and laminating it, the heat resistance of the resin molded body or the metal molded body can be improved. The effectiveness as a laminating material can be evaluated by the solder heat resistance shown in the examples.
[0075] The cross-linked aromatic polyester resin composition has good solvent resistance because it is difficult to dissolve even when immersed in a solvent (especially an organic solvent). Therefore, the cross-linked aromatic polyester resin composition can be suitably used, for example, as a laminate material.
[0076] The cross-linked aromatic polyester resin composition has good storage stability at room temperature. That is, even when stored at a predetermined temperature for a predetermined period, the gel fraction hardly changes. In addition, even when stored at a predetermined temperature for a predetermined period, it exhibits softening behavior similar to that before storage.
[0077] A cross-linked aromatic polyester resin composition can be used as a main component of self-adhesives, self-repairing materials, or molding materials.
[0078] As a self-restoring material, it can be used, for example, as a material for paint.
[0079] Since cross-linked aromatic polyester resin compositions have good moldability and extrusion moldability, they are useful as molding materials and can be used, for example, as materials for 3D printers or as materials for filament molded articles.
[0080] In addition, the cross-linked aromatic polyester resin composition can be used as a material for a network structure. A network structure is a structure in which parts of filament molded bodies are connected to each other. The network structure can be manufactured by melting the cross-linked aromatic polyester resin composition, extruding the molten material from a nozzle, and solidifying the extruded material while welding it.
[0081] The content of the cross-linked aromatic polyester resin composition in the solid content of the above self-adhesive, self-restoring material, or molding material is preferably 60 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, and may be 100 mass%.
[0082] The present application claims the benefit of priority based on Japanese Patent Application No. 2020-174488 filed on October 16, 2020. The entire contents of the specification of the said Japanese Patent Application No. 2020-174488 are incorporated herein by reference.
[0083] Examples
[0084] To explain the present invention in more detail, examples and comparative examples are provided below, but the present invention is not limited in any way by the examples. Furthermore, each measurement value described in the examples and comparative examples was measured by the following method. Also, unless otherwise specified, "parts" means "parts by mass" and "moles" means "parts by mole".
[0085] Polymerization example of a polymer polyol (A1-1)
[0086] 30 molar parts of terephthalic acid, 69 molar parts of isophthalic acid, 1 molar part of trimellitic anhydride, 15 molar parts of 2-methyl-1,3-butanediol, 85 molar parts of 1,6-hexanediol, and 0.2 molar parts of tetrabutyl titanate were injected into a reaction vessel equipped with a stirrer, a thermometer, and an outlet cooler. The temperature was gradually increased to 250°C, and an esterification reaction was carried out while removing the effluent water from the system. After the esterification reaction was completed, initial polymerization was carried out under gradually reduced pressure to 10 mmHg, the temperature was increased to 250°C, and subsequent polymerization was carried out under pressure of 1 mmHg or less until a predetermined torque was achieved. Subsequently, the pressure was returned to atmospheric pressure using nitrogen, 1 molar part of trimellitic anhydride was added, and the reaction was carried out at 220°C for 30 minutes to obtain a polymeric polyol (A1-1). The composition and characteristic values of the polymer polyol (A1-1) obtained in this way are shown in Table 1. Each measurement evaluation item was performed according to the method described below.
[0087] Polymerization example of a polymer polyol (A1-2)
[0088] 50 molar parts of terephthalic acid, 50 molar parts of isophthalic acid, 55 molar parts of ethylene glycol, 45 molar parts of 2,2-dimethyl-1,3-propanediol, and 0.2 molar parts of tetrabutyl titanate were injected into a reaction vessel equipped with a stirrer, a thermometer, and an outlet cooler. The temperature was gradually increased to 250°C, and an esterification reaction was carried out while removing the effluent water from the system. After the esterification reaction was completed, initial polymerization was carried out under gradually reduced pressure to 10 mmHg, the temperature was increased to 250°C, and subsequent polymerization was carried out under pressure of 1 mmHg or less until a predetermined torque was achieved, thereby obtaining a polymeric polyol (A1-2). The composition and characteristic values of the polymeric polyol (A1-2) obtained in this manner are shown in Table 1. Each measurement and evaluation item was performed according to the method described below.
[0089] Polymerization example of a polymer polyol (A1-3)
[0090] 50 molar parts of terephthalic acid, 49 molar parts of isophthalic acid, 1 molar part of trimellitic anhydride, 83 molar parts of 2-methyl-1,3-butanediol, 17 molar parts of 1,4-butanediol, and 0.2 molar parts of tetrabutyl titanate were injected into a reaction vessel equipped with a stirrer, a thermometer, and an outlet cooler. The temperature was gradually increased to 250°C, and an esterification reaction was carried out while removing the effluent water from the system. After the esterification reaction was completed, initial polymerization was carried out while gradually reducing the pressure to 10 mmHg, and the temperature was increased to 250°C. Subsequently, a subsequent polymerization was carried out at a pressure of 1 mmHg or less until a predetermined torque was achieved. Afterward, the pressure was returned to atmospheric pressure using nitrogen, 1 molar part of trimellitic anhydride was added, and the reaction was carried out at 220°C for 30 minutes to obtain a polymeric polyol (A1-3). The composition and characteristic values of the polymer polyol (A1-3) obtained in this way are shown in Table 1. Each measurement evaluation item was performed according to the method described below.
[0091] Polymerization example of a polymer polyol (A1-4)
[0092] 40 molar parts of terephthalic acid, 39 molar parts of isophthalic acid, 20 molar parts of adipic acid, 1 molar part of trimellitic anhydride, 58 molar parts of 2-methyl-1,3-butanediol, 42 molar parts of 1,4-butanediol, and 0.2 molar parts of tetrabutyl titanate were injected into a reaction vessel equipped with a stirrer, a thermometer, and an esterification reaction was carried out while slowly increasing the temperature to 250°C and removing the effluent water from the system. After the esterification reaction was completed, initial polymerization was carried out while slowly decreasing the pressure to 10 mmHg, increasing the temperature to 250°C, and subsequent polymerization was carried out at 1 mmHg or less until a predetermined torque was achieved. Subsequently, the pressure was returned to atmospheric pressure with nitrogen, 1 molar part of trimellitic anhydride was added, and the reaction was carried out at 220°C for 30 minutes to obtain a polymeric polyol (A1-4). The composition and characteristic values of the polymer polyol (A1-4) obtained in this way are shown in Table 1. Each measurement evaluation item was performed according to the method described below.
[0093] Polymerization example of a polymer polyol (A1-5)
[0094] 30 molar parts of terephthalic acid, 64 molar parts of isophthalic acid, 5 molar parts of sebacic acid, 1 molar part of trimellitic anhydride, 28 molar parts of 2-methyl-1,3-butanediol, 55 molar parts of 1,4-butanediol, 17 molar parts of 1,4-cyclohexanedimethanol, and 0.2 molar parts of tetrabutyl titanate were injected into a reaction vessel equipped with a stirrer, a thermometer, and an esterification reaction was carried out while slowly increasing the temperature to 250°C and removing the effluent water from the system. After the esterification reaction was completed, initial polymerization was carried out while slowly decreasing the pressure to 10 mmHg, the temperature was increased to 250°C, and subsequent polymerization was carried out at 1 mmHg or less until a predetermined torque was achieved. Afterwards, the pressure was returned to atmospheric pressure with nitrogen, 1 mole of trimellitic anhydride was added, and the reaction was carried out at 220°C for 30 minutes to obtain a polymeric polyol (A1-5). The composition and characteristic values of the polymeric polyol (A1-5) obtained in this way are shown in Table 1. Each measurement evaluation item followed the method described below.
[0095] As a polymer polyol (T5652), polycarbonate diol "T5652" manufactured by Asahi Kasei Co., Ltd. (number average molecular weight 2000) was used.
[0096] Synthesis example of an aromatic polyester resin (A-1) containing carboxyl groups in its side chains
[0097] 80 parts of polymer polyol (A1-1), 20 parts of polymer polyol (A1-2), 2.6 parts of pyromolic anhydride, and 100 parts of toluene were injected into a reaction vessel equipped with a stirrer, a thermometer, and a reflux tube, and dissolved in toluene while gradually increasing the temperature to 80°C. After dissolution was complete, 0.05 parts of triethylamine were added as a reaction catalyst, and the reaction was carried out for 24 hours while gradually increasing the temperature to 105°C. After confirming the completion of the reaction by IR (infrared spectroscopy), the solution was diluted with 54 parts of toluene to obtain a solution of aromatic polyester resin (A-1) containing carboxyl groups in its side chains with a solid content of 40%. The composition and characteristic values of the aromatic polyester resin (A-1) containing carboxyl groups in its side chains obtained in this way are shown in Table 2.
[0098] Synthesis example of an aromatic polyester resin (A-2) containing carboxyl groups in its side chains
[0099] 80 parts of polymer polyol (A1-3), 20 parts of polymer polyol (A1-2), 2.6 parts of pyromolic anhydride, and 100 parts of toluene were injected into a reaction vessel equipped with a stirrer, a thermometer, and a reflux tube, and dissolved in toluene while gradually increasing the temperature to 80°C. After dissolution was complete, 0.05 parts of triethylamine were added as a reaction catalyst, and the reaction was carried out for 24 hours while gradually increasing the temperature to 105°C. After confirming the completion of the reaction by IR, the solution was diluted with 54 parts of toluene to obtain a solution of aromatic polyester resin (A-2) containing carboxyl groups in its side chains with a solid content of 40%. The composition and characteristic values of the aromatic polyester resin (A-2) containing carboxyl groups in its side chains obtained in this way are shown in Table 2.
[0100] As an aromatic polyester resin (A-3), a polymeric polyol (A1-2) was used.
[0101] Preparation of an aromatic polyester resin (A-4) containing carboxyl groups in its side chains
[0102] 25 molar parts maleic acid, 25 molar parts adipic acid, 50 molar parts bis-2-hydroxyethyl terephthalate (BHET), and 0.5 molar parts scandium triplate were injected into a 50 ml glass flask equipped with a stirrer, and homogenization was performed at 100°C. After dissolving the raw materials, the pressure in the system was gradually reduced to 5 mmHg over 30 minutes, and a polycondensation reaction was carried out at 110°C for 4 hours under a vacuum of 0.3 mmHg or less, after which the contents were extracted and cooled. Subsequently, an aromatic polyester resin (A-4) containing carboxyl groups in the side chain, which includes carboxyl groups at multiple points in the side chain, was prepared by Michael addition of the thiol group of thioglycolic acid to the double bond site of maleic acid. The composition and characteristic values of the obtained aromatic polyester resin (A-4) containing carboxyl groups in the side chain are shown in Table 3.
[0103] Preparation of an aromatic polyester resin (A-5) containing carboxyl groups in its side chains
[0104] An aromatic polyester resin (A-5) containing carboxyl groups in its side chains was synthesized in the same manner as an aromatic polyester resin (A-4) containing carboxyl groups in its side chains, provided that the injection ratio was changed, and an evaluation was performed in the same manner as that of the aromatic polyester resin (A-4) containing carboxyl groups in its side chains. The evaluation results are shown in Table 3.
[0105] Synthesis example of an aromatic polyester resin (A-6) containing carboxyl groups in its side chains
[0106] 70 parts of polymer polyol (A1-4), 30 parts of polymer polyol (A1-2), 2.5 parts of pyromolic anhydride, and 100 parts of toluene were injected into a reaction vessel equipped with a stirrer, a thermometer, and a reflux tube, and dissolved in toluene while gradually increasing the temperature to 80°C. After dissolution was complete, 0.05 parts of triethylamine were added as a reaction catalyst, and the mixture was reacted for 24 hours while gradually increasing the temperature to 105°C. After confirming the completion of the reaction by IR, the solution was diluted with 54 parts of toluene to obtain a solution of aromatic polyester resin (A-6) containing carboxyl groups in its side chains with a solid content of 40%. The composition and characteristic values of the aromatic polyester resin (A-6) containing carboxyl groups in its side chains obtained in this way are shown in Table 2.
[0107] Synthesis example of an aromatic polyester resin (A-7) containing carboxyl groups in its side chains
[0108] 80 parts of polymer polyol (A1-5), 20 parts of polycarbonate diol "T5652" manufactured by Asahi Kasei Co., Ltd., 2.8 parts of pyromolic anhydride, and 100 parts of toluene were injected into a reaction vessel equipped with a stirrer, a thermometer, and a reflux tube, and dissolved in toluene while gradually increasing the temperature to 80°C. After dissolution was complete, 0.05 parts of triethylamine were added as a reaction catalyst, and the reaction was carried out for 24 hours while gradually increasing the temperature to 105°C. After confirming the end of the reaction by IR, the solution was diluted with 54 parts of toluene to obtain a solution of aromatic polyester resin (A-7) containing carboxyl groups in its side chains with a solid content of 40%. The composition and characteristic values of the aromatic polyester resin (A-7) containing carboxyl groups in its side chains obtained in this way are shown in Table 2.
[0109] [ Table 1 ]
[0110]
[0111] [ Table 2 ]
[0112]
[0113] [ Table 3 ]
[0114]
[0115] Number Average Molecular Weight (Mn)
[0116] Samples [polymer polyols (A1-1 to A1-5), aromatic polyester resins containing carboxyl groups in their side chains (A-1 to A-7)] were dissolved or diluted in tetrahydrofuran to a sample concentration of approximately 0.5 mass%, and the resulting solution was filtered through a polytetrafluoroethylene membrane filter with a pore diameter of 0.5 μm to serve as the measurement sample. The number-average molecular weight was measured by gel permeation chromatography using tetrahydrofuran as the mobile phase and a differential refractometer as the detector. The flow rate was set to 1 mL / min, and the column temperature to 30°C. Showa Denko KF-802, 804L, and 806L columns were used. Monodisperse polystyrene was used as the molecular weight standard. However, if the sample did not dissolve in tetrahydrofuran, N,N-dimethylformamide was used instead of tetrahydrofuran. Low molecular weight compounds (oligomers, etc.) with a number average molecular weight of less than 1000 were not counted and were omitted.
[0117] <Sanga>
[0118] 0.2 g of the sample [polymer polyol (A1-1 to A1-5), aromatic polyester resin containing carboxyl groups in its side chain (A-1 to A-7)] was dissolved in 20 ml of chloroform, and titrated with a 0.1 N potassium hydroxide ethanol solution using phenolphthalein as an indicator. From this titration amount, the number of mg of KOH consumed for neutralization was converted into an amount per 1 g of resin to calculate the acid value (mgKOH / g).
[0119] Carboxylate number
[0120] The number of carboxyl groups can be calculated by the following method. For example, if the result of the acid value is A (mgKOH / g), the number of moles of carboxyl groups per 1 g of aromatic polyester resin (A) containing carboxyl groups in the side chain can be expressed as A / 56.1 (mmol / g), since the molecular weight of KOH is 56.1 g / mol. If the number average molecular weight of the aromatic polyester resin (A) containing carboxyl groups in the side chain is B (g), the number of carboxyl groups in the polymer can be expressed as A / 56.1 × B / 1000 (mol), and this is the number of carboxyl groups per polymer chain (N COOH ...did it as ).
[0121] Glass transition temperature
[0122] Using a differential scanning calorimeter "DSC220" manufactured by Seiko Denshi Kogyo Co., Ltd., 5 mg of the sample [polymer polyol (A1-1 to A1-5), aromatic polyester resin containing carboxyl groups in its side chain (A-1 to A-7)] was placed in an aluminum pan, sealed by pressing the lid, held at 250°C for 5 minutes, then rapidly cooled with liquid nitrogen, and subsequently measured from -100°C to 300°C at a heating rate of 20°C / min. The inflection point of the obtained curve was set as the glass transition temperature.
[0123] Example 1
[0124] A film-shaped cross-linked aromatic polyester resin composition (hereinafter referred to as a cross-linked aromatic polyester resin film) was prepared as follows.
[0125] 50 molar parts of 1,4-butanediol diglycidyl ether as an epoxy compound (B) were dissolved in NMP (N-methyl-2-pyrrolidone) for every 100 molar parts of the carboxyl groups of an aromatic polyester resin (A-1) containing carboxyl groups in its side chains, such that the ratio of carboxyl groups to epoxy groups was 1 / 1 (number of functional groups) relative to 100 molar parts of the carboxyl groups. Next, separately, an ester exchange catalyst Zn(OAc)2 was dissolved in 20 molar parts of NMP (N-methyl-2-pyrrolidone). These two solutions were mixed in a Teflon (registered trademark) mold, and then the solvent was evaporated over a heater at 40°C. A cross-linked aromatic polyester resin film (thickness 0.7 mm) was obtained by heating this mixed sample at 140°C for 3 hours. The results are shown in Table 4.
[0126] Examples 2–8, Comparative Examples 1–5
[0127] Examples 2 to 8 and Comparative Examples 1 to 5 were performed by changing the aromatic polyester resin (A-1) containing a carboxyl group in the side chain and the epoxy compound (B) to those shown in Table 4, and changing the formulation amounts to those shown in Table 4 in the same manner as in Example 1. The results are shown in Table 4.
[0128] The epoxy compounds (B) used in Table 4 are as follows.
[0129] “jER630” (product name) (triglycidyl para-aminophenol) manufactured by Mitsubishi Chemical Co., Ltd.
[0130] Multifunctional epoxy compound "TETRAD-X" (trade name) manufactured by Mitsubishi Gassugaku Co., Ltd. (N,N,N',N'-tetraglycidyl-m-xylenediamine)
[0131] (Absorbance measurement by infrared spectroscopy)
[0132] The infrared absorption spectrum of the obtained cross-linked aromatic polyester resin film was measured using the ATR method (total internal reflection measurement) under the following conditions with an Agilent Technologies Co., Ltd. "Cary 660 FTIR." The number of integrated measurements was 16. 1730 cm⁻¹ originating from the ester bond -1 Absorbance in the vicinity (A 1730 ) is 1730±10 cm -1 Let the value of the absorption peak height having an absorption maximum in the region be 3200-3600 cm originating from the hydroxyl group. -1 Absorbance in the vicinity (A 3200-3600 ) is 3200–3600 cm -1 The value was set to the height of the absorption peak having an absorption maximum in the nearby region. Additionally, the baseline was defined as the line connecting the skirts on both sides of each absorption maximum peak. The absorbance ratio was calculated from the obtained absorbance according to the following formula.
[0133] (Absorbance ratio) = A 3200-3600 / A 1730
[0134] In Table 4, 1730±10 cm -1 The peak position of the absorption peak having an absorption maximum in the region, and 3200–3600 cm -1 The peak positions of the absorption peaks having absorption maxima in the region were each indicated.
[0135] [ Table 4-1 ]
[0136]
[0137] [ Table 4-2 ]
[0138]
[0139] [ Table 4-3 ]
[0140]
[0141] (Softening temperature)
[0142] The softening temperature was determined from the inflection point of the change in linear expansion coefficient of the sample (crosslinked aromatic polyester resin film) from room temperature to 300°C using the “TMA7100” manufactured by HITACHI. The measurement was performed under a nitrogen gas atmosphere with a fine constant tension (30 mN) applied to prevent bending of the sample. In addition, the initial jig distance was 15 mm. If the inflection point could be observed, the corresponding temperature was indicated, and if it could not be observed, it was indicated as -.
[0143] (Self-adhesive)
[0144] Two cross-linked aromatic polyester resin films (width 4 mm × length 2 cm × thickness 0.7 mm) were overlapped at one end by about 1 cm, and a two-layer cross-linked aromatic polyester resin film was prepared by applying a temperature above the softening temperature, a pressure of 400 kPa, and a pressure time of 2 hours. Self-adhesion was defined as ○ for the two-layer laminated portion being bonded, and self-adhesion as × for the portion not being bonded.
[0145] (Remodeling)
[0146] A cross-linked aromatic polyester resin film (width 4 mm × length 2 cm × thickness 0.7 mm) was wound onto a spatula, its ends were secured with tape, and the film was fixed to the spatula and subjected to a heat treatment process. As part of the heat treatment process, the film was left at a high temperature (softening temperature + approximately 20°C) for 2 hours and then cooled to room temperature. After cooling, the deformed cross-linked polyester resin film was removed from the spatula. When the film was removed from the spatula, if the deformed cross-linked aromatic polyester resin film maintained its wound state, it was rated as reformability ○; if it did not maintain its wound state and returned to its original flat state, it was rated as reformability ×. Additionally, if a portion of the cross-linked aromatic polyester resin film melted and could not be evaluated, it was rated as -.
[0147] (Damage repair)
[0148] A scratch (depth of approximately 0.1 mm) was made on the surface of a cross-linked aromatic polyester resin film (length 1.5 cm × width 1.5 cm × thickness 0.7 mm) using a cutter. Afterward, a heat treatment process was performed on the cross-linked aromatic polyester resin film. As part of the heat treatment process, the film was left at a high temperature (softening temperature + approximately 20°C) for 10 minutes and then cooled to room temperature. After the heat treatment process, if the scratch disappeared and the cross-linked aromatic polyester resin film became scratch-free on the surface, the damage repairability (self-repairability) was rated as ○, and if the scratch remained, the damage repairability (self-repairability) was rated as ×. Additionally, if a portion of the cross-linked aromatic polyester resin film melted and could not be evaluated, it was indicated as -.
[0149] (5% weight loss temperature)
[0150] Measurements were taken using the “DTG-60” thermal analyzer manufactured by Shimadzu Seisakusho. 10 g of the sample (cross-linked aromatic polyester resin film) was placed in an aluminum pan, and the weight loss was measured when the temperature was increased from room temperature to 400°C at a rate of 5°C / min. The temperature at which the weight decreased by 5% (5% weight loss temperature) was used as an indicator of heat resistance.
[0151] (90° fill strength)
[0152] A test specimen measuring 20 mm in length × 50 mm in width was cut from the obtained cross-linked aromatic polyester resin film (thickness 0.7 mm). The cut test specimen was placed on a PET film (manufactured by Toyobo Co., Ltd.) with a thickness of 25 μm, and a PET film of the same type was placed on the test specimen to form a three-layer structure of “PET film / cross-linked aromatic polyester resin film / PET film,” and each layer was bonded by applying pressure and heating at 170°C, 2 MPa, and 280 seconds using a heat press. The laminate obtained by bonding was used as a 90° peel strength evaluation sample.
[0153] In addition, a 90° peel strength evaluation sample was prepared under the same conditions except that a polyimide film (PI, "Apical" (registered trademark) manufactured by Kaneka Co., Ltd., thickness 12.5 μm) was used instead of the above PET film, and the three-layer composition of "PI / cross-linked aromatic polyester resin film / PI" was prepared. In addition, for the cross-linked aromatic polyester resin films obtained in Examples 5 and 6, a sample was also prepared by changing the heating temperature in the heat press to 200°C.
[0154] In addition, instead of the above PET film, a rolled copper foil (thickness 20 μm) and a polyimide film (PI, "Apical" (registered trademark) manufactured by Kaneka Co., Ltd., thickness 12.5 μm) were used to produce a 3-layer composition of "Cu / crosslinked aromatic polyester resin film / PI," and a 90° peel strength evaluation sample was prepared under the same conditions except for this. In addition, for the crosslinked aromatic polyester resin films obtained in Examples 5 and 6, a sample was also prepared by changing the heating temperature in the heat press to 200°C.
[0155] The 90° peel strength was measured using an Autograph AG-Xplus manufactured by Shimadzu Seisakusho at 25°C and a tensile speed of 50 mm / min. Based on the measured 90° peel strength, the adhesion of the film was evaluated according to the following criteria. The evaluation results are shown in Table 5 below. Additionally, "-" indicates that the test was not performed.
[0156] <Evaluation Criteria>
[0157] ◎: 1.0 N / mm or higher
[0158] ○: 0.5 N / mm or more and less than 1.0 N / mm
[0159] △: 0.35 N / mm or more and less than 0.5 N / mm
[0160] ×: Less than 0.35 N / mm
[0161] (Moldability)
[0162] A sample obtained from a cross-linked aromatic polyester resin film (thickness 0.7 mm) was cut to a width of 5 mm × length of 5 mm and placed in a mold. The mold used was fabricated by cutting a circle with a diameter of 8 mm into a 1 mm thick Teflon (registered trademark) sheet. Subsequently, pressure and heating were applied using a heat press. The pressure condition was set to 4 MPa, and the heating condition was set to softening temperature + 30°C for 15 minutes. Moldability was evaluated as ○ if the cross-linked aromatic polyester resin film segment could be molded into the mold shape, and × if it could not be molded. The evaluation results are shown in Table 5 below. Additionally, "-" indicates that the test was not performed.
[0163] (Extrusion moldability)
[0164] A sample of 6 g of the obtained cross-linked aromatic polyester resin film (thickness 0.7 mm), cut into a width of 5 mm × length of 5 mm, was fed into a HAAKE twin-screw extruder "MiniLab" in three separate batches at a barrel temperature of 150°C, and the screw rotation speed was 50 min -1 After the sample was fed into the barrel, the mixture was kneaded for 5 minutes, and then extruded from the barrel. After kneading, the extrusion moldability was evaluated as ○ if the mixture could be extruded and a shaped molded body was obtained, and as × if the mixture could not be extruded and a shaped molded body was not obtained. The evaluation results are shown in Table 5 below. In addition, “-” indicates that the test was not performed.
[0165] (Solder heat resistance)
[0166] The obtained cross-linked aromatic polyester resin film was bonded to a copper-clad laminate with a thickness of 49 μm (manufactured by Nittetsu Chemical & Material Co., Ltd., ESPANEX series, Cu / polyimide / Cu = 12 μm / 25 μm / 12 μm) so that the glossy surface of the rolled copper foil was in contact. The laminate samples for evaluating solder heat resistance were obtained by pressing at 170°C for 280 seconds under a pressure of 20.4 kgf / cm². If the softening temperature of the cross-linked aromatic polyester resin film was 150°C or higher and the film was not sufficiently bonded at a pressing temperature of 170°C, the pressing temperature was increased to 180°C or 200°C to produce the laminate samples. A test specimen measuring 2.0 cm × 2.0 cm was cut from the obtained laminate sample, and the specimen was floated for 1 minute in a solder bath with the bath temperature adjusted from 250°C to 280°C in 10°C increments to measure the upper limit temperature at which no expansion occurred. Specifically, the specimen was floated for 1 minute in a solder bath at a temperature of 250°C; if no expansion occurred, it was floated for 1 minute in a solder bath at a temperature of 260°C, 270°C, or 280°C, and this process was repeated until expansion occurred, and the upper limit temperature at which no expansion occurred was measured. The measurement results are shown in Table 5 below. A higher upper limit temperature at which no expansion occurs indicates better solder heat resistance. In addition, for Examples 5 and 6, solder heat resistance was evaluated for a sample prepared at a press temperature of 170°C and a sample prepared at a press temperature of 200°C, respectively.
[0167] (Room temperature storage stability)
[0168] The room temperature storage stability of the obtained cross-linked aromatic polyester resin film was evaluated based on the rate of change in gel fraction and softening behavior.
[0169] (1) Rate of change of gel fraction
[0170] First, the gel fraction of the obtained cross-linked aromatic polyester resin film is measured. The gel fraction was measured by the following method.
[0171] 0.125 g of the obtained cross-linked aromatic polyester resin film was weighed and immersed in 25 mL of methyl ethyl ketone at room temperature for 2 hours. Then, only the remaining gel component was dried in a vacuum dryer at 80°C for 1 hour, and its mass was measured. The gel fraction was measured according to the following formula.
[0172] Gel fraction (%) = (Weight of remaining gel component after drying ÷ 0.125) × 100
[0173] Next, the cross-linked aromatic polyester resin film was stored at a constant temperature of 5°C, 25°C, or 40°C for 6 months, and the gel fraction was measured by the method described above after 6 months. Based on the gel fraction at the start of storage and the gel fraction after 6 months of storage, the rate of change from the gel fraction at the start of storage was calculated. The rate of change was defined as the absolute value of the difference between the gel fraction (%) before and after 6 months, as shown in the following formula.
[0174] Rate of change = Gel fraction after 6 months (%) - Gel fraction at the start of storage (%)
[0175] Evaluations were conducted by marking ○ for a change rate of less than 10%, △ for a change rate of 10% or more and 25% or less, and × for a change rate exceeding 25%. The evaluation results are shown in Table 5 below. Additionally, "-" indicates non-implementation.
[0176] (2) Softening behavior
[0177] When the obtained cross-linked aromatic polyester resin film was stored at 25°C for 6 months, the presence or absence of softening behavior due to bond exchange reactions was evaluated by stress relaxation measurement. MCR302 (manufactured by Anton Paar) was used for stress relaxation measurement, and stress relaxation tests were performed at temperatures of 100°C, 150°C, and 180°C. The tests were conducted under an N2 gas atmosphere. For the test specimens, disc-shaped samples with a diameter of 8 mm × a thickness of 0.7 mm, cut from the cross-linked aromatic polyester resin film, were used.
[0178] After storing at 25°C for 6 months, cases where softening behavior was exhibited when a stress relaxation test was performed at any of the temperatures of 100°C, 150°C, or 180°C were evaluated as ○, and cases where softening behavior was not exhibited when a stress relaxation test was performed at any of the temperatures of 100°C, 150°C, or 180°C were evaluated as ×. The evaluation results are shown in Table 5 below. The fact that stress relaxation is observed after storage at 25°C for 6 months indicates that the softening characteristics due to bond exchange are maintained even after storage, and that there is no change from the initial behavior during the long-term storage period at room temperature.
[0179] (Content)
[0180] Three samples were prepared for each level by cutting the obtained cross-linked aromatic polyester resin film (thickness 0.7 mm) into a width of 5 mm × length of 5 mm and placing one sample into each screw bottle. To each, 3 mL of ethanol, dimethylformamide (DMF), or tetrahydrofuran (THF) was added, and the samples were left to stand at room temperature for 5 hours. After standing for 5 hours, the solvent resistance was evaluated as Good ◎ if there was no change compared to before immersion, Solvent Resistance Good ○ if swelling of the sample was observed but it did not dissolve, and Solvent Resistance Ineffective × if it dissolved. The evaluation results are shown in Table 5 below. Additionally, "-" indicates that the test was not performed.
[0181] (90° peel strength upon heating)
[0182] The 90° peel strength upon heating was measured for the "Cu / crosslinked aromatic polyester resin film / PI" among the above 90° peel strength evaluation samples using a thermostatic chamber (manufactured by Shimadzu Seisakusho, THERMOSTATIC CHAMBER) at the softening temperature of each sample listed in Table 5 + 30°. For the measurement of 90° peel strength, an Autograph AG-Xplus manufactured by Shimadzu Seisakusho was used, and measurements were taken at a temperature of the softening temperature of each sample + 30° at a tensile speed of 50 mm / min. Based on the measured 90° peel strength upon heating, the peelability of the laminate was evaluated according to the following criteria. The evaluation results are shown in Table 5 below. Additionally, "-" indicates that the test was not performed.
[0183] <Evaluation Criteria>
[0184] ◎: Less than 0.35 N / mm
[0185] ○: 0.35 N / mm or more and less than 0.5 N / mm
[0186] △: 0.5 N / mm or more and less than 1.0 N / mm
[0187] ×: 1.0 N / mm or more
[0188] The cross-linked aromatic polyester resin film obtained in Example 1 was cut into fine resin shapes (width 5 mm × length 5 mm × thickness 0.7 mm), melted at a temperature of 200°C, and solidified by discharging it into cooling water at a single-hole discharge rate of 1.0 g / min from a nozzle having an effective surface with a width of 40 cm and a length of 4 cm, wherein annular solid orifices with a hole diameter of 1.0 mm were arranged at intervals of 4 mm. Specifically, cooling water was placed 10 cm below the discharge position, and a pair of receiving conveyors were arranged parallel to a stainless steel endless net with a width of 50 cm at intervals of 3 cm so that they partially protruded above the water surface. The film was then fed into the cooling water at a speed of 1.0 m / min while fusing the contact parts and fitting both sides together to solidify it. Subsequently, it was dried in a hot air dryer at 70°C for 15 minutes and then cut into a predetermined size. As a result, a network structure with a thickness of 3 cm and a density of 0.060 g / cm³ was obtained.
[0189] [ Table 5-1 ]
[0190]
[0191] [ Table 5-2 ]
[0192]
[0193] [ Table 5-3 ]
[0194]
[0195] Examples 1, 3, and 4
[0196] The cross-linked aromatic polyester resin films of Examples 1, 3, and 4 are a system in which 50 mol of an epoxy compound (B) (carboxyl group / epoxy group = 1 / 1 (number of functional groups)) and 20 mol of zinc acetate are mixed with 100 mol of carboxyl groups of polyester resins (A-1, A-2, A-4), and characteristics such as softening, self-adhesion, remolability, and damage repairability are exhibited through ester bond exchange.
[0197] Example 2
[0198] The cross-linked aromatic polyester resin film of Example 2 is a system in which the zinc acetate used in Example 1 was reduced from 20 molar parts to 10 molar parts, and the softening temperature increased from 120°C to 150°C. It is thought that the ester bond exchange activity decreased because the amount of ester exchange catalyst added was small.
[0199] Examples 5 and 6
[0200] A system was prepared by mixing a 3-function epoxy or a 4-function epoxy as an epoxy compound (B) with a polyester resin (A-1) identical to that of Example 1, such that the ratio of carboxyl groups to epoxy groups is 1 / 1 (number of functional groups) with respect to 100 molar parts of the carboxyl groups of the polyester resin (A-1), and the softening temperature increased by more than 50°C compared to Example 1. It was confirmed that the softening temperature tended to increase as the crosslinking density of the obtained crosslinked aromatic polyester resin film increased.
[0201] Examples 7, 8
[0202] The cross-linked aromatic polyester resin films of Examples 7 and 8 are a system in which 50 mol of an epoxy compound (B) (carboxyl group / epoxy group = 1 / 1 (number of functional groups)) and 20 mol of zinc acetate are mixed with 100 mol of carboxyl groups of polyester resin (A-6, A-7), and properties such as softening due to ester bond exchange, self-adhesion, remolability, damage repairability, and heat resistance are exhibited.
[0203] The cross-linked aromatic polyester resin films of Examples 1 to 8 had high 90° peel strength and were useful as adhesives. In addition, moldability, extrusion moldability, solder heat resistance, room temperature storage stability, and solvent resistance were also excellent. Furthermore, it was found that the 90° peel strength was low when heated to the softening temperature + 30°, making it easy to peel.
[0204] Comparative Example 1
[0205] Polyester resin (A-3) has a polymer structure that does not possess carboxyl groups in its side chains and, since carboxyl groups exist only at the ends, three-dimensional crosslinking does not proceed, so physical properties could not be evaluated.
[0206] Comparative Example 2
[0207] The cross-linked aromatic polyester resin composition using a polyester resin (A-5) with a very high acid value had a high absorbance ratio, and the softening temperature and the 5% weight loss temperature were nearly equal. It is thought that the decomposition of the cross-linked aromatic polyester resin proceeds near the softening temperature. This implies that the high absorbance ratio of the cross-linked aromatic polyester resin composition means there are many secondary OH groups generated by the reaction between the carboxyl groups and epoxy groups of the polymer side chains. In other words, it is thought that because the cross-linking density of the cross-linked aromatic polyester resin composition is very high, the molecules themselves are difficult to move, making it difficult for ester bond exchange to occur.
[0208] Comparative Examples 3, 4, and 5
[0209] Examples 1, 5, and 6 are systems that do not contain an ester exchange catalyst (zinc acetate). When an aromatic polyester resin containing carboxyl groups in its side chains is mixed with only an epoxy compound and cured, the crosslinking reaction proceeds, but the ester bond exchange reaction at high temperatures does not proceed, so softening behavior at high temperatures, self-adhesion, remolability, and damage repairability are not exhibited. It is considered to be a general thermosetting polyester resin. Industrial applicability
[0210] The cross-linked aromatic polyester resin composition of the present invention has heat resistance of 230°C or higher (especially 300°C or higher) and excellent self-adhesion, remolability, and damage repairability in a temperature range above the softening temperature. For this reason, it is particularly useful as an adhesive or paint that can be used repeatedly.
Claims
Claim 1 A cross-linked aromatic polyester resin composition comprising a cross-linked aromatic polyester resin (C) and an ester exchange catalyst (D), satisfying the following (1) to (2), wherein the molar ratio (carboxyl group:ester exchange catalyst) of the ester exchange catalyst (D) to the carboxyl group of the aromatic polyester resin (A) having a carboxyl group in a side chain is 100:10 to 100:40: (1) The cross-linked aromatic polyester resin (C) is a reaction product of an aromatic polyester resin (A) having a carboxyl group in a side chain and an epoxy compound (B). (2) When the cross-linked aromatic polyester resin composition is measured by infrared spectroscopy, the wavenumber originating from the ester bond is 1730 cm⁻¹ -1 Absorbance of the peak in the vicinity (A 1730 Regarding ), wavenumber derived from the hydroxyl group 3200–3600 cm -1 Absorbance of the peak in the vicinity (A 3200-3600 The ratio of ) (A 3200-3600 / A 1730 ) is 0.005 or greater and 0.038 or less. Claim 2 A cross-linked aromatic polyester resin composition according to claim 1, wherein the acid value of the aromatic polyester resin (A) containing a carboxyl group in the side chain is 5 mgKOH / g or more and 120 mgKOH / g or less. Claim 3 A cross-linked aromatic polyester resin composition according to claim 1 or 2, wherein the number average molecular weight of the aromatic polyester resin (A) containing a carboxyl group in the side chain is 8000 or more. Claim 4 A cross-linked aromatic polyester resin composition according to claim 1 or 2, wherein the molar ratio (carboxyl group:epoxy group) of the epoxy compound (B) to the carboxyl group of the aromatic polyester resin (A) having a carboxyl group in the side chain is 100:50 to 100:
150. Claim 5 A cross-linked aromatic polyester resin composition according to claim 1 or 2, wherein the number average molecular weight of the epoxy compound (B) is 100 or more and 500 or less. Claim 6 delete Claim 7 A method for preparing a cross-linked aromatic polyester resin composition, comprising a process of mixing an aromatic polyester resin (A) having an acid value of 5 mgKOH / g or more and 120 mgKOH / g or less and containing a carboxyl group in a side chain, an epoxy compound (B), and an ester exchange catalyst (D), and heating to crosslink, wherein the molar ratio (carboxyl group:ester exchange catalyst) of the ester exchange catalyst (D) to the carboxyl group in the side chain of the aromatic polyester resin (A) having a carboxyl group in a side chain is 100:10 to 100:
40. Claim 8 A self-adhesive agent containing a cross-linked aromatic polyester resin composition as described in claim 1 or 2. Claim 9 A self-repairing material containing a cross-linked aromatic polyester resin composition as described in claim 1 or 2. Claim 10 A molding material containing a cross-linked aromatic polyester resin composition as described in claim 1 or 2.
Citation Information
Patent Citations
Heattsensitive carboxylated copolymer adhesive and its production method
JP1977005849A
Polyester type adhesive and sheet-like laminate using the same
JP2013039784A
Use of a fluid binder composition in the preparation of sealing compounds for closure systems for JARS and bottles
WO1995023187A1
Cross-linked polyester resin and its production
JP1998087959A